Effect of the modification of a silica xerogel by sodium dodecyl sulfate for the adsorption of crystal violet dye in aqueous medium - Buzato, Gabriel Vinicius (2021)
The incorrect discharge of dyes has been one of the main causes of water pollution. Actions to reduce these impacts have been performed, and an alternative is through the adsorption of dyes on silica-based materials such as xerogels. Very few experiments, however, show the modification of silica-based xerogels using surfactants for dye adsorption applications. In this paper, we report the preparation of silica-based xerogels (SiO2) to explore the influence of the surface modification with sodium dodecyl sulfate (SDS) in the adsorption behavior of an organic dye, crystal violet (CV), from water using Ultra-Violet visible spectroscopy. The textural properties of the xerogels, SiO2 unmodified (SiO2-UN) and SiO2-SDS modified (SiO2-SDS) showed that the samples are mesoporous. The surface charges for SiO2-UN and SiO2-SDS were negative at experimental conditions as shown by pH point of zero charge (PZC) data. The adsorption capacity of SiO2-SDS for VC was superior to that of SiO2-UN and, in addition, SiO2-SDS had a higher rate constant. This behavior is probably ascribed to the presence of SDS micelles formed into the pores of wet silica xerogels, suggesting electrostatic interaction between anionic head groups from the micelles and cationic VC.  The adsorption kinetics were best fitted by the pseudo-second order model. The equilibrium data were best described to the Langmuir isotherm model. The qm values of CV on SiO2-SDS reached 25,8 mg g−1 and 1,59 mg g−1 on SiO2-UN. These findings are important to help in the treatment of industrial wastewater.